Development of a Cardiovascular Simulator Incorporating a Phantom Simulation of the Arterial System - Foley, Liam (Auckland University of Technology, 2021)
A mock circulatory loop was constructed to test a new blood pressure device under development. The loop was intended to replicate a range of cardiac conditions with the implementation of an artificial arterial tree. An in-depth literature review was conducted on the previous construction on mock circulatory loops and arterial phantoms. The methods employed previously were analysed and implemented in this project. Lost core casting methods were used to create complex artery phantoms, using 3D printed moulds and silicone elastomers, yielding an arterial tree that was dimensionally and functionally accurate in reproducing pulse wave amplification and arterial wall compliance. A synthetic ventricle pump was developed in conjunction with a variable compliance chamber and peripheral resistance. The pump consists of a synthetic ventricle inside a water-filled chamber with a motor actuating a piston to change the volume, successfully reproducing the flow desired. The compliance chamber emulated a bladder accumulator to reproduce capacitances as desired, and a motor actuated gate valve simulates peripheral resistance. The overall system successfully reproduced human pressures and flows, with sufficient damping being observed due to the compliance chamber and the elastic vessels.
Keywords: Cardiovascular; Mock Circulatory Loop; Phantom Arteries; Blood Pressure